Obesity worsens mitochondrial quality control and does not protect against skeletal muscle wasting in murine cancer cachexia - Thomas D. Cardaci; Brandon N. VanderVeen; Brooke M. Bullard; Sierra J. McDonald; Christian A. Unger; Reilly T. Enos; Daping Fan; Kandy T. Velázquez; Norma Frizzell; Espen E. Spangenburg; E. Angela Murphy (Wiley, 2024)
Abstract Background More than 650 million people are obese (BMI > 30) worldwide, which increases their risk for several metabolic diseases and cancer. While cachexia and obesity are at opposite ends of the weight spectrum, leading many to suggest a protective effect of obesity against cachexia, mechanistic support for obesity's benefit is lacking. Given that obesity and cachexia are both accompanied by metabolic dysregulation, we sought to investigate the impact of obesity on skeletal muscle mass loss and mitochondrial dysfunction in murine cancer cachexia. Methods Male C57BL/6 mice were given a purified high fat or standard diet for 16 weeks before being implanted with 106 Lewis lung carcinoma (LLC) cells. Mice were monitored for 25 days, and hindlimb muscles were collected for cachexia indices and mitochondrial assessment via western blotting, high‐resolution respirometry and transmission electron microscopy (TEM). Results Obese LLC mice experienced significant tumour‐free body weight loss similar to lean (−12.8% vs. −11.8%, P = 0.0001) but had reduced survival (33.3% vs. 6.67%, χ2 = 10.04, P = 0.0182). Obese LLC mice had reduced muscle weights (−24%, P < 0.0354) and mCSA (−16%, P = 0.0004) with similar activation of muscle p65 (P = 0.0337), and p38 (P = 0.0008). ADP‐dependent coupled respiration was reduced in both Obese and Obese LLC muscle (−30%, P = 0.0072) consistent with reductions in volitional cage activity (−39%, P < 0.0001) and grip strength (−41%, P < 0.0001). TEM revealed stepwise reductions in intermyofibrillar and subsarcolemmal mitochondrial size with Obese (IMF: −37%, P = 0.0009; SS: −21%, P = 0.0101) and LLC (IMF: −40%, P = 0.0019; SS: −27%, P = 0.0383) mice. Obese LLC mice had increased pAMPK (T172; P = 0.0103) and reduced FIS1 (P = 0.0029) and DRP1 (P < 0.0001) mitochondrial fission proteins, which were each unchanged in Lean LLC. Further, mitochondrial TEM analysis revealed that Obese LLC mice had an accumulation of damaged and dysfunctional mitochondria (IMF: 357%, P = 0.0395; SS: 138%, P = 0.0174) in concert with an accumulation of p62 (P = 0.0328) suggesting impaired autophagy and clearance of damaged mitochondria. Moreover, we observed increases in electron lucent vacuoles only in Obese LLC muscle (IMF: 421%, P = 0.0260; SS: 392%, P = 0.0192), further supporting an accumulation of damaged materials that cannot be properly cleared in the obese cachectic muscle. Conclusions Taken together, these results demonstrate that obesity is not protective against cachexia and suggest exacerbated impairments to mitochondrial function and quality control with a particular disruption in the removal of damaged mitochondria. Our findings highlight the need for consideration of the severity of obesity and pre‐existing metabolic conditions when determining the impact of weight status on cancer‐induced cachexia and functional mitochondrial deficits.